2022
DOI: 10.1038/s41598-021-04517-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress and the unfolded protein response in skeletal muscle of subjects suffering from peritoneal sepsis

Abstract: We provide a descriptive characterization of the unfolded protein response (UPR) in skeletal muscle of human patients with peritoneal sepsis and a sepsis model of C57BL/6J mice. Patients undergoing open surgery were included in a cross-sectional study and blood and skeletal muscle samples were taken. Key markers of the UPR and cluster of differentiation 68 (CD68) as surrogate of inflammatory injury were evaluated by real-time PCR and histochemical staining. CD68 mRNA increased with sepsis in skeletal muscle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…This was associated with increased mRNA levels of the chemokine CCL2 and the receptor CD68 —a marker for macrophage infiltration in response to skeletal injury. In line with these findings, mice subjected to CLP also showed a higher expression of Xbp1 in muscle tissues, but in contrast to humans, also of Atf4 , and BiP ( 142 ). Of note, other animal studies had shown that ER stress and UPR counteract cancer-associated muscle wasting ( 147 ).…”
Section: The Unfolded Protein Response During Sepsissupporting
confidence: 73%
See 1 more Smart Citation
“…This was associated with increased mRNA levels of the chemokine CCL2 and the receptor CD68 —a marker for macrophage infiltration in response to skeletal injury. In line with these findings, mice subjected to CLP also showed a higher expression of Xbp1 in muscle tissues, but in contrast to humans, also of Atf4 , and BiP ( 142 ). Of note, other animal studies had shown that ER stress and UPR counteract cancer-associated muscle wasting ( 147 ).…”
Section: The Unfolded Protein Response During Sepsissupporting
confidence: 73%
“…Regarding the UPR, it was shown that patients with peritoneal sepsis had a higher expression of XBP1 , but not of ATF4 or ATF6 in the muscle ( 142 ). This was associated with increased mRNA levels of the chemokine CCL2 and the receptor CD68 —a marker for macrophage infiltration in response to skeletal injury.…”
Section: The Unfolded Protein Response During Sepsismentioning
confidence: 99%
“…However, the accumulation of unfolded proteins in the endoplasmic reticulum (ER) can also activate the ISR. According to the results described in the literature [ 42 , 43 , 44 ], we demonstrated that the LPS injection promotes the expression of ER stress-related genes by activating transcription factors 6 and 4 (ATF6 and ATF4), which promotes the transcription of genes involved in the ER quality control and apoptosis, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…The ER is pivotal to the maintenance of cellular homeostasis. 137 Studies have shown that ER stress is frequently an initiating factor for incomplete autophagy (Table 1). ER stress could disturb the intracellular ion levels, 60 which affects lysosomal enzyme activity and lysosomal acidity.…”
Section: Crosstalk Of Signaling Pathwaysmentioning
confidence: 99%
“…There are extensive crosstalks between above signals in the process of incomplete autophagy (Figures 3 and 4). The ER is pivotal to the maintenance of cellular homeostasis 137 . Studies have shown that ER stress is frequently an initiating factor for incomplete autophagy (Table 1).…”
Section: Signaling Molecules and Pathways Regulating Incomplete Autop...mentioning
confidence: 99%